Measuring the Impact of Employee Training and Development Programs Before and After Covid-19: A Case Study - Uning Heri Gagarin; Jumadiah Wardati; Elia Agus Victoria (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to develop and test an impact measurement system that integrates global supply chain risks with a company’s financial performance. Supply chain risk—arising from both internal and external factors can lead to operational disruptions, increased costs, and disturbed cash flows, thereby affecting key financial performance indicators such as ROA, ROE, NPM, CR, and DER. The research uses a quantitative approach with Structural Equation Modeling (SEM) based on AMOS, along with scenario analysis and what-if simulations to assess the effects of specific disruptions. The findings indicate that financial risk and operational risk are the dominant factors exerting significant negative effects on financial performance: financial risk notably reduces ROA and ROE, while operational risk affects NPM through higher costs and margin compression. Geopolitical and environmental risks, though showing more moderate effects, still influence overall operational stability and financial performance. Managerial recommendations include supplier diversification, implementing Supply Chain Finance (SCF), using real-time monitoring technologies and developing risk-specific contingency plans.